Towards a Realistic and Self-Contained Biomechanical Model of the Hand - Sancho-Bru, Joaquín L.; Pérez-González, Antonio; Mora, Marta C.; León, Beatriz E.; Vergara, Margarita; Iserte, José L.; Rodríguez-Cervantes, Pablo J.; Morales, Antonio (IntechOpen, 2011)
None